Peran Kepuasan Pelanggan Memoderasi Pengaruh Kualitas Pelayanan dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan E-Commerce pada Generasi Z di Jabodetabek - Nurjanah, Anisa; Sriminarti, Nurul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The purpose of this study was to determine the role of customer satisfaction in moderating the influence of service quality and customer experience on customer loyalty. This study uses a survey method with a questionnaire as its instrument. The respondents of this study were 160 respondents who used e-commerce in the Jabodetabek area. The sampling process used a nonprobability sampling technique using a quantitative approach that was associative using primary data. The method used was the PLS-SEM method with WARP-PLS 7.0 as its software. These results indicate that Service Quality has a positive and significant effect on Customer Loyalty, Customer Experience has a positive and significant effect on Customer Loyalty, Customer Satisfaction moderates the relationship between Service Quality and Customer Loyalty significantly, although with a small moderation contribution, thus the customer satisfaction variable can be said to be a Quasi Moderation. And Customer satisfaction is unable to moderate Customer Experience on Customer Loyalty but is significant when used as a direct variable, so from this the customer satisfaction variable can be called Pure Moderation.